KONSEPSI PENDIDIKAN KARAKTER MENURUT AL-ZARNUJI DAN THOMAS LICKONA - Saefudin Zuhri; Diding Nazmudin; Ahmad Asmuni (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
AbstractCharacter education is now indeed a major issue in education. In addition to being part of the process of forming the morals of children of the nation, character education is expected to be able to be the main foundation in increasing the degree and dignity of the Indonesian nation.By using a qualitative descriptive method with the type of research Library Research (literature review), The data source was obtained from several scientific works of al-Zarnuji and Thomas Lickona as primary data and supported by other secondary data.By definition Lickona thoroughly examines character education that leads to conclusions Character education is not just having an interactive dimension, in a sense, strengthening the intellectual morals of students so that they become strong individuals who stand the test, but must also be synergistic both personally and socially. While al-Zarnuji relies more on the concept of moral education taught in Islam.There are differences in principles, objectives and methods of application. The purpose of character education for Thomas Lickona is more oriented to social good, while al-Zarnuji leads to social and spiritual dimensions. Keywords:  Character Education, al-Zarnuji, Thomas Lickona.